2004
DOI: 10.1023/b:mcbi.0000012835.08001.8f
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory action of a new lectin from Xerocomus chrysenteron on cell-substrate adhesion

Abstract: Lectins are carbohydrate-binding proteins which potentially link to cell surface glycoconjugates and affect cell proliferation. We investigated the effect of a new lectin from the mushroom Xerocomus chrysenteron (XCL) on cell proliferation using adherent and suspension cell lines. XCL caused a dose-dependent inhibition of proliferation of the adherent cell lines NIH-3T3 and HeLa. Several experiments suggest that disruption of cell-substrate adhesion is the main factor affecting cell growth inhibition. (i) No a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 24 publications
0
15
1
Order By: Relevance
“…As an example, XCL was endocytosed by various animal and human cell lines and caused inhibition of proliferation of some of these cell lines (Francis et al 2003;Marty-Detraves et al 2004). A second issue is the way the protein is applied to the crop plant.…”
Section: Potential Applicationsmentioning
confidence: 99%
“…As an example, XCL was endocytosed by various animal and human cell lines and caused inhibition of proliferation of some of these cell lines (Francis et al 2003;Marty-Detraves et al 2004). A second issue is the way the protein is applied to the crop plant.…”
Section: Potential Applicationsmentioning
confidence: 99%
“…XCL has potent insecticidal activity, 20 and blocks the proliferation of several cell lines by disrupting the cell-substrate adhesion. 21 XCL is similar to ABL, which also expresses selective cytotoxicity against malignant epithelial cell lines by blocking the sequence-dependent nuclear protein import. 47,48 SRL shares with ABL and XCL similar carbohydrate specificities for N-acetyl galactosamine and the TF-antigen.…”
Section: Comparison To Other Fungal Lectinsmentioning
confidence: 99%
“…19 XCL also shows antiproliferative activity on different cell lines and interestingly exhibits potent insecticidal activity. 20,21 Lectins from Coprineus cinerea (CGL2) 22 and Agrocybe cylindracea (ACG) 23 share a common carbohydrate recognition domain with galectins, a large family of β-galactoside-binding animal lectins with a highly conserved carbohydrate recognition domain (CRD). CGL2 has unique sugar specificity and binds strongly to the blood group A tetrasaccharide GalNAcα1-3 [Fucα1-2]Galβ1-4Glc; 24 on the other hand, ACG recognizes sialoconjugates.…”
Section: Introductionmentioning
confidence: 99%
“…This effect is coupled to a dramatic change of the organization of the actin cytoskeleton. 10 Following its binding to the cell surface, XCL is internalized via the clathrin-dependent pathway and the protein is rapidly delivered to late endosome/lysosome compartments. 11 Our studies on XCL indicated potent insecticidal activity towards two insect models.…”
Section: Introductionmentioning
confidence: 99%